Comparative analysis of key performance indicators of Islamic index - Sarılı, Selin; Çakmur Yıldırtan, Z. Dina (My University, 2016)
Islamic index in general is the stock exchange index that includes stocks traded in the national and international market, the companies operating in accordance with Islamic law. First in 1990, it was introduced in the US Wall Street Stock Exchange. Islamic indices have a great importance to be able to measure the stock performance of companies operating in accordance with Islamic principles. In this study Standard and Poor’s, Dow Jones, Morgan Stanley, and the Financial Times Stock Exchange Islamic Indices have been included in the study on a monthly frequency and to compare the performance beta values are estimated by creating the index single index model. In the study using the Capital Asset Pricing Models (CAPM), expected return for indices were estimated. In addition, to compare portfolio performance Sharpe Ratio, Treynor Ratio, Jensen Performance Ratio is calculated.
Keywords: Islamic indices,CAPM,Sharpe,Treynor,Jensen